Prevalence of thermotolerant species of Campylobacter and their biotypes in children and domestic birds and dogs in Southern Chile Prevalência de espécies termotolerantes de Campylobacter e seus biotipos em crianças, aves domésticas e cães no sul do Chile - Heriberto Fernández; Karen Kahler; Rossana Salazar; Marco Antonio Ríos (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
The prevalence of thermotolerant Campylobacter in diarrhoeic and healthy children as well as in dogs, hens, ducks and pigeons was determined in Southern Chile. Campylobacter were found in 34.5% of the faecal samples examined. The isolation rate of Campylobacter in diarrhoeic and healthy children was 16.3% and 6.4% respectively. Despite C.jejuni was always more frequent than C. coli, the latter was isolated with a high frequency (29%) from patients with diarrhoea. C.jejuni and C. coli biotypes I and II were found in healthy and diarrhoeic children and were predominant in all the animals species studied. This may point out towards the possible origin of strains infecting children. Foi determinada, no sul do Chile, a prevalência de espécies termotolerantes de Campylobacter e seus biotipos, em crianças normais e diarréicas, bem como em cães e aves domésticas. Campylobacter foi isolado em 34,5% do total das amostras estudadas sendo sua frequência de isolamento de 16,3% e 6,4% nas crianças com diarréia e normais, respectivamente. C. jejuni foi a espécie mais freqüente. Porém, C. coli foi isolado em 29% das crianças com diarréia. Somente os biotipos I e II, tanto de C. jejuni como de C. coli, foram isolados das crianças, os quais foram também os mais frequentemente encontrados nos animais, sugerindo uma possível associação epidemiológica entre eles